Existence of solution to n-person noncooperative games and minimax regret equilibria with set payoffs. Issue 7 (3rd May 2022) - Zhang, Yu; Chen, Tao; Chang, Shih-sen
Abstract : In this paper, by virtue of the Kakutani–Fan–Glicksberg fixed point theorem and a nonlinear scalarization function, we first obtain an existence theorem of general n -person noncooperative games problems with set payoffs. Then, we also obtain existence theorems of minimax regret equilibria and ϵ -minimax regret equilibria with scalar set payoffs. Some examples are given to illustrate our results.